PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN ASAM-BASA DI KELAS XI IPA SMA N 5 PEKANBARU - Erna, Maria; ', Lenni; ', Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This research aims to know the improve of students learning achievement by using Learning Cycle 7E model on the topic of the Acid-Base of Elements in class XI IPA senior high school (SMAN) 5 Pekanbaru. This research was experimental research with pretest-postest design. The sample of this research were students of class XI IPA 1 as the experimental research and students of class XI IPA 2 as a control class that has been randomly selected after a test of normally and homogenity test. Experiment class is a class that is applied Learning Cycle 7E model while the control class was not. The analysis techniques consist of 3 techniques that are normality test was used Liliefors test to verify data is normally distributed, homogeneity test was used variance test and t-test to see same ability learning of samples and hypothesis test was used t-test to validate the hypothesis. Based on analysis of the data obtained tcount> ttable is 2,32>1,67, it is mean that the implementation of Learning Cycle 7E model can improved students learning achievement on the topic of the Acid-Base of Elements in class XI IPA senior high school (SMAN) 5 Pekanbaru. Category improve student achievment in the classroom experiment with a normalized gain value (N-gain) of 0,83 is included in the high category.Keywords: Learning Cycle 7E, Learning Achievement, Acid-Base